Management of a Type I Hypersensitivity Reaction to IV Etoposide in a Woman with a Yolk Sac Tumor: A Case Report - David Starks; Deborah Prinz; Amy Armstrong; Lindsay Means; Steven Waggoner; Robert DeBernardo (Hindawi Limited, 2011)
Type I hypersensitivity reactions to intravenous administration of etoposide are extremely rare. Etoposide is an essential component of several chemotherapy regimens used in gynecologic oncology, and discontinuation of this drug during a course of treatment should only be due to severe patient intolerance. We report the successful use of intravenous etoposide phosphate as a substitute drug in a patient with a yolk sac tumor who manifested a Type I hypersensitivity to intravenous etoposide. The patient ultimately completed all 4 cycles of bleomycin, etoposide, cisplatin (BEP) using etoposide phosphate as a substitute drug.